EARLY INSTRUCTION IN ACCOUNTING. - Wildman, J. R. (The Accounting Review, 1926)
Abstract The article presents information on instruction in Accounting at the New York University as experienced by the author himself. In this University men who undertook to teach accounting when the school was organized admitted that they had very little idea of what it was all about. They got some men from the practical field, out of accountants' offices, to come up in the evening and talk to a small class of about thirty students. They were full sized books of accounts and they were accompanied by a syllabus of transactions and the members of that class were required to work out these transactions, put them into the books and make some statements from them. This proved to be of very great interest. The Instructor or professor who handled the Class in problems was a very busy practicing accountant He gathered a number of C.P.A. problems that was the basis for the whole thing in the early years; and he worked out his own solutions on pieces of paper which he kept In the lower left-hand drawer of his desk, filed away with the problems. There were no pedagogue in the group of faculty. They were hard-headed, practical accountants, most of them, but they had very few and hazy ideas about teaching.